Sidonius Apollinaris in the Quattrocento - Hernández Lobato, Jesús (Cuadernos de Filología Italiana, 2012)
This paper studies the reception of the late antique writer Sidonius Apolinaris (430/431-c. 487 d.C.) within the cultural scene of the Quattrocento. First, it analyses Sidonius’ deep influence on the works of the humanist Angelo Poliziano, who was particularly close to the principles of the sophisticate late antique poetics –he was in a sense its «re-inventor» in the Renaissance. Secondly, the paper traces Sidonius’ presence in other Italian and Spanish authors of that time and the circulation of his works. Finally, it highlights the erudite knowledge of Sidonius’ works demonstrated by an officially «classicist» author: Ermolao Barbaro.
Keywords: Quattrocento; reception of the Late Antique literature; Sidonius Apolinaris; Angelo Poliziano; Ermolao Barbaro.